2021
DOI: 10.3390/ani11092513
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Copper Improves Intestinal Morphology via Modulating Intestinal Stem Cell Activity in Pigs

Abstract: Copper (Cu) is an essential micronutrient for animals. Many studies have been conducted on the effects of dietary Cu on growth performance, intestinal morphology, and function of piglets. However, the underlying mechanism remains to be explored. Intestinal stem cells (ISC) drive the development and constant renewal of intestinal epithelium. Therefore, we hypothesized that dietary Cu affects piglets’ intestinal development via modulating ISC activity. A total of eighty-five 21-day-old piglets were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Adult intestinal stem cells respond to environmental cues (including dietary signals) and influence intestinal epithelium homeostasis through the alteration of its function and activity. 40,42,46,47 In recent years, phenolic acids, especially CGA, have gained substantial attention because of their potential benefits for alleviating health-related problems. Chlorogenic acid has been reported in vegetables and fruits but the most commonly studied sources are coffee and tea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adult intestinal stem cells respond to environmental cues (including dietary signals) and influence intestinal epithelium homeostasis through the alteration of its function and activity. 40,42,46,47 In recent years, phenolic acids, especially CGA, have gained substantial attention because of their potential benefits for alleviating health-related problems. Chlorogenic acid has been reported in vegetables and fruits but the most commonly studied sources are coffee and tea.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in intestinal morphology are usually accompanied by the process of epithelial cell renewal. 42,52 Intestinal epithelial cells are regenerated continuously throughout adulthood from stem cells located in the base of the intestinal crypt. Previous studies identified Lgr5 as an adult stem-cell marker in the intestine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal tract is an important organ, which is mainly responsible for digestion and absorption (19). Villus height and crypt depth are commonly used to evaluate the functional status of the small intestine (20). The crypt is considered to be a producer of villus cells, and the lower depth of crypt indicates that the intestinal villi are in good condition (21).…”
Section: Discussionmentioning
confidence: 99%
“…The sheep in the CTE treatment had a greater villus height in the duodenum, jejunum and ileum than those sheep in the CON and UTE treatments, indicating that dietary coated trace elements were beneficial to improve the absorption function of small intestinal. Previous studies reported that a single supplement of dietary trace minerals had a positive effect on the gut health of animals, such as Fe ( Zhou et al, 2020 ), Cu ( Yin et al, 2021 ), Zn ( Wang et al, 2018 ) and Se ( Samo et al, 2020 ). Replacing inorganic trace elements with complex organic trace minerals in the diet could increase the villus height in the ileum of weaned piglets ( Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%